Anti-inflammatory activity in selected Antarctic benthic organisms - Moles, Juan; Torrent, Anna; Alcaraz, M. José; Ruhí, Ramon; Avila, Conxita (Frontiers in Marine Science, 2014)
Antarctic benthos was prospected in search for anti-inflammatory activity in polar benthic invertebrates, in two different geographical areas: deep-bottoms of the Eastern Weddell Sea and shallow-waters of the South Shetland Islands. A total of 36 benthic algae and invertebrate species were selected to perform solubility tests in order to test them for anti-inflammatory activity. From these, ethanol extracts of ten species from five different phyla resulted suitable to be studied in cell macrophage cultures (RAW 264.7). Cytotoxicity (MTT method) and production of inflammatory mediators (prostaglandin E2, leukotriene B4, interleukin-1) were determined at three extract concentrations (50, 125, 250 g/mL). Bioassays resulted in four different species showing anti-inflammatory activity corresponding to three sponges: Mycale (Oxymycale) acerata, Isodictya erinacea, and I. toxophila; and one hemichordate: Cephalodiscus sp. These results show that Antarctic sessile invertebrates may have great value as a source of lead compounds with potential pharmaceutical applications.